Development of a Simple Micriscope from Used Goods as a Science Learning Media - Muhammad Ma'arif Ikhsannudin (Indonesian Journal of Applied Research (IJAR), 2022)
The purpose of this study is expected to be able to develop a microscope from used goods that are used as a mechanism for learning science in schools. By using a simple microscope from used goods, it can make it easier for educators and students in the teaching and learning process. Furthermore, this research also has a stage in the manufacturing process or called the method. The method used is called the 4D development method, where this method has the stages of Define, Design, Develop, and Disseminate. According to the results of the research conducted, a simple microscope from used goods is very effective as a learning medium. A simple microscope from scrap can also ease the burden on the school in purchasing a microscope due to the high price of a microscope. The results obtained were quite good and in accordance with the cellphone camera at the time the study was carried out. Despite this, this simple microscope has its advantages and disadvantages. The advantage of this simple microscope is that this microscope is made of materials around us so that students themselves have no difficulty making it. While the weakness lies in this simple microscope which can only see objects with a magnification of 10 times the original and the quality is then in accordance with the cellphone camera used.